Financial evaluation of in vitro olive trees production with real options - Perea-Gómez, Lorena; García-Salazar, José Alberto; López-Reyna, María del Carmen; Arellano-Ostoa, Gregorio (Instituto de Ecología, A.C., 2022)
Projects for the establishment of biotechnology companies are difficult to evaluate because they are in scenarios of risk and uncertainty. The objective of this work was to assess the financial feasibility of a commercial in vitro culture laboratory for the propagation of olive trees (Olea europaea L.). The project was evaluated with the traditional method through the calculation of the net present value (NPV), internal rate of return (IRR), discount rate (CRR), and benefit-cost ratio (B/C), and with the real options approach using binomial trees. The latter method considered the price volatility of the product and the probability of success of each of the project’s five stages (establishment, multiplication, rooting, acclimatization, and nursery) of the project. The results obtained with the traditional method indicate that the project should be rejected because the NPV value was MXN -1 498 656, the IRR was 13%, the CRR was 25%, and the B/C was 0.83. The results of the evaluation with the real options method indicate that each of the five stages of the project could be carried out in the two scenarios analyzed, considering that the total NPV was positive in each stage and, in addition, the value of the next stage was more significant than the value of the previous one. With this method, it was possible to determine the actual value of the project and the opportune moment to abandon it; therefore, it is recommended that investors use it when making decisions on high-risk investments in biotechnology projects.